A Review Study on the Trends of Psychological Challenges, Coping Ways, and Public Support During the COVID-19 Pandemic in the Vulnerable Populations in the United States - Kumar, Rakesh; Singh, Anand; Mishra, Rahul; Saraswati, Ushasi; Bhalla, Jaideep; Pagali, Sandeep (Frontiers in Psychiatry, 2022)
Background: The covid-19 pandemic resulted in significant mortality and morbidity in the United States. The mental health impact during the pandemic was huge and affected all age groups and population types. This rapid review was carried out to investigate trends in psychological impacts, coping ways, and public support during the Covid-19 pandemic crisis in the U.S. Methods: We undertook a rapid review of the literature following the Covid-19 pandemic in the U.S. We searched PubMed as it is widely available database, for observational and experimental studies that reported the psychological effects, coping ways, and public support on different age groups and HCWs during the Covid-19 pandemic. Results: We included thirty-five studies in our review and reported data predominantly from the U.S. population. Our review findings indicate that covid-19 has a considerable impact on the psychological well-being of various age groups differently and especially in the elderly population and Health care workers (HCWs). Review findings suggest that factors like children, elderly population, female gender, overconcern about family, fear of getting an infection, personality, low spirituality, and lower resilience levels were at a higher risk of adverse mental health outcomes during this pandemic. Systemic support, higher resilience levels, and adequate knowledge were identified as protecting and preventing factors. All the included studies in our review investigated and surveyed the psychological impacts, coping skills, and public support system during this pandemic Conclusions: The evidence to date suggests that female gender, child and elderly population, and racial factors have been affected by a lack of support for psychological well-being. Further, research using our hypothesized framework might help population groups to deal with a pandemic-associated mental health crisis, and in that regard analysis of wider societal structural factors is recommended.